(untitled) (Journal of Tikapur Multiple Campus, 2014)
This paper investigates remittance flow to Nepal during last ten fiscal years in absolute term and relative to GDP, export earning and foreign exchange reserve. It also tries to investigate relation of remittance with current account balance and balance of payment surplus. In addition, it also makes comparison between remittance inflow and foreign exchange reserves. The external sector macroeconomic variables show the positive relation between remittance growth and increasing trade deficit. The empirical studies carried out across the nation have also suggested that remittance has more causality on the consumption pattern as well as the import pattern, and less on investment pattern. Furthermore, with available literatures, this paper discusses the implications of channelizing the remittance flow into productive capital.